'Weak' or 'Strong' Sustainable Consumption? Efficiency, Degrowth, and the 10 Year Framework of Programmes. (December 2013) - Hobson, Kersty
Although reducing levels and impacts of contemporary consumption and production has been a pivotal socioenvironmental goal for decades, global resource use continues to grow rapidly, particularly across the Asia-Pacific region. Responses such as the '10 Year Framework of Programmes on Consumption and Production Patterns' (10YFP)—an outcome of the 2012 Rio+20 Summit—suggest that nothing short of highly coordinated and multilevel concerted efforts are required to begin to address such trends. However, some commentators fear that the 10YFP will default to 'weak' forms of sustainable consumption intervention, focusing on efficiency and technological innovation. By contrast, many are calling for 'strong' interventions such as those expounded by the degrowth movement. With this paper I examine both these weak and strong approaches to sustainable consumption, and argue that—although this dichotomy describes two divergent streams of thought and practice—there are conceptual and practice-based spaces where they intersect. Along with a much-needed expansion of the geographical scope of current research and practice, I thus argue that these spaces present one way forward for work in this field.